1997
DOI: 10.1038/36342
|View full text |Cite
|
Sign up to set email alerts
|

The prostaglandin receptor EP4 triggers remodelling of the cardiovascular system at birth

Abstract: Survival of newborn placental mammals depends on closure of the ductus arteriosus (DA), an arterial connection in the fetus which directs blood away from the pulmonary circulation and towards the placenta where oxygenation occurs. Here we show that morphological changes resulting in closure of the DA in mice are virtually identical to those observed in larger mammals, including humans, and that maintenance of the DA in the open, or patent, state in fetal mice is dependent on prostaglandin synthesis. This requi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
228
3
1

Year Published

2000
2000
2012
2012

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 335 publications
(248 citation statements)
references
References 22 publications
12
228
3
1
Order By: Relevance
“…Moreover, we and others have previously shown that ductus arteriosus closure is dependent on activation of the EP4 receptor for PGE 2 (43,44), yet mPGES1-deficient mice undergo normal closure of the ductus arteriosus (21,32). Taken together, these data indicate that there are alternative, mPGES1-independent pathways for PGE 2 synthesis in the intact animal.…”
Section: Discussionsupporting
confidence: 60%
“…Moreover, we and others have previously shown that ductus arteriosus closure is dependent on activation of the EP4 receptor for PGE 2 (43,44), yet mPGES1-deficient mice undergo normal closure of the ductus arteriosus (21,32). Taken together, these data indicate that there are alternative, mPGES1-independent pathways for PGE 2 synthesis in the intact animal.…”
Section: Discussionsupporting
confidence: 60%
“…The ductus arteriosus closes following birth as a consequence of a complex process involving smooth muscle cell proliferation, migration and extracellular matrix deposition. Prostaglandins are important mediators for triggering this process, as demonstrated by the patent ductus and postnatal hypoxic death of mice lacking prostaglandin receptor E4 (26) and of mice lacking both cyclooxygenase 1 and 2 (27). Although we have not observed any postnatal death in our 129-apoE mice, we have found that both the aortic and pulmonary artery sides of the ductus arteriosus remain open in many of the adult 129-apoE mice and form funnellike pockets.…”
Section: Discussionmentioning
confidence: 68%
“…EP 1 is a constrictive receptor and EP 3 induces a decline in cAMP, inhibiting smooth muscle relaxation (Narumiya and FitzGerald 2001). The main receptor responsible for PGE 2 -induced DA relaxation varies among mammalian species and was reported as EP 4 in rabbits (Smith 1998;Smith et al 1994;Smith and McGrath 1995), mice (Nguyen et al 1997), rats , lambs (Waleh et al 2004), baboon (Waleh et al 2004), and humans (Leonhardt et al 2003), and as EP 2 in pigs (Bhattacharya et al 1999) and lambs (Bouayad et al 2001). The cAMP-inhibiting EP 3 receptor is also present in the rabbit and piglet DA, modulating the dilating eVect of PGE 2 (Bhattacharya et al 1999;Smith 1998;Smith et al 1994;Smith and McGrath 1995).…”
Section: Introductionmentioning
confidence: 99%